VARIASI WAKTU RADIASI GELOMBANG MIKRO TERHADAP INSIDENSI JAMUR PATOGEN TULAR BENIH DAN PERKECAMBAHAN PADI - Cahya, Fajar Tri; Puspita, Fifi; Armaini, Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect and get the best microwave radiation period to control the pathogenic fungus of rice seeds while maintaining viability and seed vigor. This research was conducted in Plant Disease Laboratory, Plant Ecophysical Laboratory of Agriculture Faculty and Synthesis Organic Laboratory Faculty of Mathematics and Natural Sciences University of Riau, Pekanbaru in February 2018. The study was using complete randomized design (RAL). The parameters observed were kind of seed born pathogenic fungus, incidence of seed born pathogenic fungus, seed viability and vigor through seed germination test, first count test and index value test. The detection results indicate that the isolate of the suspected pathogenic fungus of rice seed was Rhizoctonia sp. (isolate PK-1 and PK-7), Pyricularia sp. (isolate PK-3), Curvularia sp. (isolate PK-5 and PK-9) and unidentified fungus (isolate PK-2, PK-4, PK-6 and PK-8). The total incidence of fungi from rice seed on 60 seconds of radiation effectively reduced the incidence percentage to 38% lower than the duration of other radiation and without radiation. Radiation treatment for 15 seconds was the best treatment obtained because it was able to suppress the incidence percentage by 84.67% with a 92% seed germination, 49.67% first count sprout and 1.5%/etmal speed sprout.Keywords: microwaves,radiation period, rice seeds, seed born pathogenic fungus, seed germination